PENGARUH PROFITABILITS, LIKUIDITAS DAN CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK - Dewa Ayu Putu Karisma Adiputri; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2021)
Tax aggressiveness is actions taken by companies with the aim of reducing the payment of tax burdens throught tax avoidance or tax evasion. This research was conducted to examine the effect of Profitability, Liquidity, and Capital Intensity on Tax Aggresiveness in basic industrial and chemical manufacturing companies listed on the Indonesia Stock Exchange (IDX) with the observation time of the 2015-2019 period. The population of this research is 61 companies with 15 companies that have fulfilled the criteria as samples. The profitability variable in this study can be measured using ROA (Return On Assets), the liquidity variable is measured using CR (Current Ratio), capital intensity is measured by dividing total net fixed assets by total company assets, and for tax aggressiveness it can be measured using CETR (Cahs Effectif Tax Rate). The results in this study are that profitability has a negative and significant effect on tax aggressiveness, liquisity has a positive and significant effect on tax aggressiveness and capital intensity has no effect on tax aggressiveness.